PENCAPAIAN KOMPETENSI SISWA KELAS X PROGRAM KEAHLIAN TEKNIK OTOMOTIF SMK BHINNEKA KARYA SURAKARTA PADA MATA PELAJARAN KOMPETENSI DASAR OTOMOTIF TAHUN PELAJARAN 2015/2016 - Rizky Noor Aditama; Husin Bugis; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The objectives of this research are to investigate: (1) the Basic Competency Standard of the Automotive Expertise Program in Grade X of Bhinneka Karya Vocational High School of Surakarta in academic year 2015/2016; (2) the students’ learning result; and (3) the students’ ways of thinking to improve their learning result through the application of the 2013 curriculum. This research used the descriptive qualitative method, which described its objects of research holistically based on the reality in the field and which aimed at describing the facts being studied systematically and accurately. The data sources of the research were the teachers and the students in Grade X TO B of the Automotive Expertise Program of Bhinneka Karya Vocational High School of Surakarta. Its data were collected through observation, in-depth interview, and documentation. They were analyzed by using the interactive model of analysis comprising data collection, data reduction, data display, and conclusion drawing or verification. The attainment of competency particularly in the Automotive Basic Competency subject matter of the students of Bhinneka Karya Vocational High School of Surakarta can be improved through the application of  2013 curriculum. The application of 2013 curriculum is more efficient in assessing the students’ attitude, knowledge, skill, and spirit aspects as indicated by the results of their final test of the second semester in which following the application of the 2013 curriculum, their learning achievement increased by 22.74% from 36.36% to 59.1%.